Physical Activity, Screen Time, and Sleep Duration of Children Aged 6-9 Years in 25 Countries: An Analysis within the WHO European Childhood Obesity Surveillance Initiative (COSI) 2015-2017 - Whiting, Stephen; Buoncristiano, Marta; Gelius, Peter; Abu-Omar, Karim; Pattison, Mary; Hyska, Jolanda; Duleva, Vesselka; Musić Milanović, Sanja; Zamrazilová, Hana; Hejgaard, Tatjana; Rasmussen, Mette; Nurk, Eha; et al. (Obesity facts, 2021)
BACKGROUND: Children are becoming less physically active as opportunities for safe active play, recreational activities, and active transport decrease. At the same time, sedentary screen-based activities both during school and leisure time are increasing. OBJECTIVES: This study aimed to evaluate physical activity (PA), screen time, and sleep duration of girls and boys aged 6-9 years in Europe using data from the WHO European Childhood Obesity Surveillance Initiative (COSI). METHOD: The fourth COSI data collection round was conducted in 2015-2017, using a standardized protocol that included a family form completed by parents with specific questions about their children's PA, screen time, and sleep duration. RESULTS: Nationally representative data from 25 countries was included and information on the PA behaviour, screen time, and sleep duration of 150,651 children was analysed. Pooled analysis showed that: 79.4% were actively playing for >1 h each day, 53.9% were not members of a sport or dancing club, 50.0% walked or cycled to school each day, 60.2% engaged in screen time for <2 h/day, and 84.9% slept for 9-11 h/night. Country-specific analyses of these behaviours showed pronounced differences, with national prevalences in the range of 61.7-98.3% actively playing for >1 h/day, 8.2-85.6% were not members of a sport or dancing club, 17.7-94.0% walked or cycled to school each day, 32.3-80.0% engaged in screen time for <2 h/day, and 50.0-95.8% slept for 9-11 h/night. CONCLUSIONS: The prevalence of engagement in PA and the achievement of healthy screen time and sleep duration are heterogenous across the region. Policymakers and other stakeholders, including school administrators and parents, should increase opportunities for young people to participate in daily PA as well as explore solutions to address excessive screen time and short sleep duration to improve the overall physical and mental health and well-being of children.
Keywords: Parents; pohybová aktivita; spánek; volnočasové aktivity; Physical inactivity; Europe; cvičení; Evropa; školy; mužské pohlaví; Sleep; Světová zdravotnická organizace; Pediatric Obesity; čas strávený před obrazovkou; World Health Organization; dítě; Child; Schools; sporty; ženské pohlaví; Humans; Active transport, active play; Sedentary behaviour; Screen Time; Surveillance; Exercise; Motor Activity; Sports; Female; Leisure Activities; obezita dětí a dospívajících; rodiče; lidé; Male